The Effect of EMLA Cream on Reducing Pain Due to Vaccination in Children - M. Nory Shadkam; KH. Nasiriani; J. Ayattollahe; M. Shakiba (Iran University of Medical Sciences, 2008)
Background and Aim: One of the medical procedures causing pain is vaccination. It is associated with increased anxiety, restlessness, and increased parent distress and angry. Therefore, recognition and application of pain control strategies by health care worker is necessary. The aim of the current study was to examine the effect of EMLA cream in reducing pain due to DPT vaccination.  Material and Method: A randomized controlled trial, double-blind design was selected to conduct the study. One hundred and two infants with age 4 months undergoing DPT vaccination were selected by convenient sampling and randomly allocated to either experimental or control group. Infants in experimental group received EMLA on the skin and those in control group received placebo (Vit A+D) on the skin. Symptoms associated with pain while DPT vaccination measured by ( MPBS) and crying time. Results: The results showed that the MPBS scores were significantly lower in the EMLA group (2.08±1.02) compared with the placebo group (4056±1.05) (P=0.03). The duration of crying was significantly lower in the EMLA group (6.00± 5.01sec) than in placebo group (10.42±4.34) (P=0.04). There was no statistically significant difference in side effect of intervention between two groups. Conclusions: This study showed that EMLA cream could be effective in reducing pain due to vaccination in infants. Health care workers are recommended to use EMLA cream for relieving pain, facilitating acceptance of parents to multiple injections and Promoting of quality health care